J. Jablonskis’ Relation with the Church and His Attitude towards Religion - Piročkinas, Arnoldas (Problemos, 1971)
The eminent Lithuanian linguist J. Jablonskis (1860- 1930), as well as many representatives of liberally-minded Lithuanian intelligentsia of the end of the 19th-the beginning of the 20th centuries, took an active part in the national movement and was attacked by the catholic church, whose rigidities Jablonskis defied during his lifetime and whose dogmas he criticized.